Wireless communications signal processing perspevtives - Poor, H. Vincent; Wornell, Gregory W. (Prentice-Hall signal processing series., 1998)
The book begins with detailed coverage of signal processing issues surrounding the physical layer, including efficient diversity techniques for fading channels; adaptive interference suppression in wireless systems; equalization in multiuser wireless systems; and space-time blind signal processing for wireless systems. Next, the book explores key aspects of the relationships between physical and network layers, then moving on to detailed coverage of network layer issues. These include signal processing techniques for introducing multimedia capabilities onto wireless networks; and issues of data compression. Finally, the book addresses the specialized underwater propagation environment. Together, these chapters address many of the main themes and directions now being pursued in state-of-the-art signal processing research asit relates to wireless communications. - See more at: http://www.betterworldbooks.com/wireless-communications-id-0136203450.aspx&utm_source=Affiliate&utm_campaign=Text&utm_medium=booklink&utm_term=3630151&utm_content=Homepage#sthash.Um1D1UNz.dpuf